2016
DOI: 10.1166/jnn.2016.10687
|View full text |Cite
|
Sign up to set email alerts
|

Sintering Behavior and Effect of Silver Nanowires on the Electrical Conductivity of Electrically Conductive Adhesives

Abstract: In this paper, two kinds of silver nanowires with a 160 nm average diameter ranging from 30 to 90 µm length and a 450 nm average diameter up to 100 µm length were successfully synthesized by a polyol process with FeCl3 and Na₂S as reaction inhibitor, respectively. The experimental results indicate that the morphologies and sintering behaviors of both of silver nanowires are impacted by glutaric acid and sintering temperature. The isotropically conductive adhesives (ICAs) filled with micro-sized silver flakes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, the preparation of AgNWs with a controllable structure has always been a difficult problem. In the past few years, we have been working on investigating the controllable structure, performance and applications of AgNWs [10,11,21,22,23,24,25]. Bergin and coworkers have recently reported that the transmittance of AgNW film with AgNWs of a given diameter linearly rely on area coverage and do not rely on the length of AgNWs, and that the decrease of AgNWs diameter improves optoelectronic performance only for AgNWs with less than 20 nm in diameter [26].…”
Section: Introductionmentioning
confidence: 99%
“…However, the preparation of AgNWs with a controllable structure has always been a difficult problem. In the past few years, we have been working on investigating the controllable structure, performance and applications of AgNWs [10,11,21,22,23,24,25]. Bergin and coworkers have recently reported that the transmittance of AgNW film with AgNWs of a given diameter linearly rely on area coverage and do not rely on the length of AgNWs, and that the decrease of AgNWs diameter improves optoelectronic performance only for AgNWs with less than 20 nm in diameter [26].…”
Section: Introductionmentioning
confidence: 99%